Numerical mathematical analysis, - Scarborough, James B. (Oxford and IBH ;, 1966)
The book's object to set forth in a systematic manner and as clearly as possible the most important principles, methods and processes used for obtaining numerical results and also methods and means for estimating the accuracy of such results. the treatment of all topics has been made as elementary as was consistent with soundness and in some instances with detailed explanation as the book is meant to be understood with a minimum of effortm on the part of the reader. In this edition, the enlargement is made by the addition of Trapezoidal Rule, an additional method for finding the roots numerical equations, and formulae and computing schedules for the numerical solution os simultaneous differential equations of the second order by the Runge-Kutta method.